SGLT2 inhibitors in diabetic and non-diabetic kidney transplant recipients: current knowledge and expectations - Polychronopoulou, Erietta; Bourdon, Fanny; Teta, Daniel (Frontiers in Nephrology, 2024)
The beneficial effect of sodium-glucose cotransporter-2 inhibitors (SGLT2i) have been shown recently in numerous randomized controlled trials (RCT) and systematic reviews. According to KDIGO guidelines, SGLT2i currently represent a first choice for diabetic patients with chronic kidney disease (CKD). In addition, a recent meta-analysis of 13 large led by the ‘SGLT2 inhibitor Meta-Analysis Cardio-Renal Trialists’ Consortium’ (SMART-C) provided solid evidence of SGLT2i beneficial effects in CKD or in patients with heart failure, with and without diabetes. Collectively, the patients treated with SGLT2i had a decreased risk of CKD progression, acute kidney injury (AKI), end-stage kidney disease (ESKD) or death from heart failure. Whether these cardio-renal benefits should be extrapolated to kidney transplant recipients (KTR) needs to be assessed in further studies. In this article, we report recent data accumulated so far in the literature, looking at the efficacy and safety of SGLT2i in diabetic and non-diabetic KTR. We found encouraging data regarding the use of SGLT2i in KTR with diabetes. These agents appeared to be safe, and they reduced body weight and blood pressure in this group of patients. Potential effects on kidney graft function and survival are yet to be investigated.